2016
DOI: 10.1177/0263617416675176
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate removal from aqueous solutions by using natural Jordanian zeolitic tuff

Abstract: In this study, a naturally occurring zeolitic tuff located in Jordan was investigated as a potential adsorbent for phosphate removal from aqueous solution. Adsorption kinetics and thermodynamics of phosphate adsorption under different temperatures were studied. The pseudo-second-order kinetic model adequately fitted the collected experimental data under different initial ion concentrations. The Langmuir model is found to be successfully fitting the experimental data. Thermodynamic parameters such as Gibbs's fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
(42 reference statements)
1
11
0
1
Order By: Relevance
“…Wheat straw, cotton stalks, grass clippings, rice straw, date palm residue, pine needles, bark, pea straw, sugarcane, and leaf debris are common organic materials used for mulching (Al-Rawahy et al 2011). Zeolite showed high capacity in adsorption and storage of metals (Al-zboon et al 2016), phosphate (Aljbour et al 2017), andgases (Al-Harahsheh et al 2014). In an agricultural field, it was reported that soil amendment with zeolite reduces the impact of saline water on barley plant due to the capability of zeolite for enhancing water and salt holding capacity of soil (Al-Busaidi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Wheat straw, cotton stalks, grass clippings, rice straw, date palm residue, pine needles, bark, pea straw, sugarcane, and leaf debris are common organic materials used for mulching (Al-Rawahy et al 2011). Zeolite showed high capacity in adsorption and storage of metals (Al-zboon et al 2016), phosphate (Aljbour et al 2017), andgases (Al-Harahsheh et al 2014). In an agricultural field, it was reported that soil amendment with zeolite reduces the impact of saline water on barley plant due to the capability of zeolite for enhancing water and salt holding capacity of soil (Al-Busaidi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphate removal from water and wastewater via adsorption processes offers an alternative treatment, especially if the sorbent is economical and easily available. A considerable attraction has been paid to economic and environmental concerns to the research of applying various kinds of inexpensive sorbents, such as zeolite (Aljbour et al, 2017;Zhang et al, 2014), sludge , fly ash (Novais et al, 2016), periwinkle shell (Bello and Ahmad, 2011a), and slag (Park et al, 2007). Previous research suggests that calcite, aluminum hydroxides/oxides, and iron hydroxides/oxides are significant phosphate sorbents (Karageorgiou et al, 2007;Lai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several technologies have been proposed for phosphate removal such as using natural Jordanian zeolitic tuff as an adsorbent (Aljbour et al . ) and photosynthetic microorganisms such as algae and cyanobacteria (Zhang et al . ; Burut‐Archanai et al .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity of phosphate removal processes using phosphate accumulating organisms (PAOs) under a sequential anaerobic-aerobic processes (Ramasahayam et al 2014), phosphate removal is still a bottle neck for the development of long-term recirculating aquaculture systems. Therefore, several technologies have been proposed for phosphate removal such as using natural Jordanian zeolitic tuff as an adsorbent (Aljbour et al 2016) and photosynthetic microorganisms such as algae and cyanobacteria (Zhang et al 2008;Burut-Archanai et al 2013;Rai et al 2016;Ruiz-G€ uereca & S anchez-Saavedra 2016). Using microalgae for phosphate removal is less complicated than PAOs.…”
Section: Introductionmentioning
confidence: 99%